Evaluation of the Crude Protein and Amino Acid Composition of Nigerian Monodora myristica (Ehuru) - R.C., Ekeanyanwu (Pakistan Journal of Nutrition, 2013)
Protein plays an important role in biochemical, biophysical and physiological processes. The deficiency of proteins leads to weakness, anaemia, protein energy malnutrition (Kwashiorkor and marasmus), delayed wound healing and fracture healing and also decreased resistance to infection. Proteins in the body come from both plant and animal source. Life without protein is not possible and amino acids are the building blocks of protein. The crude protein and amino acid composition of Monodora myristica seed was determined using standard analytical techniques with a view to further appraise the nutritive value. The results showed that crude protein content in percentage as 11.34%. The Total Amino Acid (TAA) of Monodora myristica seed was 65.60g/100g of crude protein. The Total Essential Amino Acid (TEAA, with Histidine) was calculated to be 47.64% of the crude protein while the Total non Essential Amino Acid (TNEAA) was calculated to be 52.36% of the crude protein. The predicted protein efficiency ratio (P-PER) was calculated to be 2.32. The content of total Essential Amino Acid (EAA) with value 26.85g/100g crude protein is lower than FAO/WHO recommended value of 36.0g/100g crude protein. Monodora myristica could be used as good sources of protein supplement in the human diet. Monodora myristica has been used as spice and condiment in food and also possess medicinal property.